The Development of an Online Course in Corrosion Engineering – A Critical Aspect in any Corrosion Management System - Gubner, Rolf; Tan, Yong; Bailey, Stuart; Lewis, Simon (NACE, 2011)
Through its ongoing partnership with Woodside Energy Ltd, Chevron Energy Technology Company and Chevron Australia Pty Ltd, Curtin University is currently developing online corrosion engineering courses for graduate students, with the aim of assisting them to become qualified corrosion engineers. The first course was offered for the first time in first semester 2011. It is an initiative that will enable Curtin University to respond to the growing demand by industry for high quality graduates with a broad understanding of corrosion issues, particularly those relevant to the oil and gas industry. Further investment into corrosion education will also provide industry with practical solutions applying corrosion management and avoiding costly corrosion damage. As the program is industry driven, the learning outcome is directly relevant to the energy and resources industry. This course is offered in a fully online format to provide flexible learning opportunities for students who may already be in the workforce and do not have the opportunity to attend a formal university based corrosion engineering classes. The Curtin University Corrosion Engineering graduate course is unique to the Australasian region and offers an opportunity to study from the home or employment location. This paper discusses our experiences and lessons learned from the preparation and online delivery of the first unit of the course. The online learning environment will be demonstrated and students currently enrolled in the course will be invited to share their thoughts with the audience.